Technology Acceptance in Developing Critical Thinking Ability: Evidence from Preparatory Stage Students - Yadav, Dheeraj; Yadav, Saroj; Yadav, Anamika (Indian Journal of Educational Technology, 2025)
This paper aims to explain the role of technology acceptance in the development of students’ critical thinking skills. Based on Technology Acceptance Model (TAM) and relevant pedagogy theories this study examines the influence of perceived usefulness, perceived ease of use and actual intention to use technology. A mixed-method approach combining structured surveys and classroom observations was essential to explore the complex interplay between technology engagement and cognitive skill development. The findings showed a significant positive relationship between students’ acceptance of technology and critical thinking ability. Students who believe technology to be useful and easy to use are more likely to exhibit inquiry, analysis, and collaborative problem-solving. Key enablers of sustained engagement and reflective learning include teacher facilitation and interactive digital environments. The study calls on curriculum designers to introduce intuitive and goal-oriented technology tools to ensure that they are in line with learning outcomes. We should prioritise strategies that increase digital engagement and critical thinking in teacher training. Educational institutions need to foster the acceptance of technology by demonstrating its educational value. This study provides an understanding of the long-term impact of technology acceptance in influencing cognitive development and problem-solving skills for the younger generation.